Tiglicamides A–C, cyclodepsipeptides from the marine cyanobacterium Lyngbya confervoides - Matthew, Susan (2009)
The Floridian marine cyanobacterium Lyngbya confervoides afforded three new cyclodepsipeptides, termed tiglicamides A–C (1–3), along with their previously reported analogues largamides A–C (4–6), all of which possess an unusual tiglic acid moiety. Their structures were deduced by one- and two-dimensional NMR combined with mass spectrometry and the absolute configurations established by chiral HPLC and Marfey’s analysis of the degradation products. Compounds 1–3 moderately inhibited porcine pancreatic elastase in vitro with IC(50) values from 2.14 to 7.28 µM. Compounds 1–6 differ from each other by one amino acid residue within the cyclic core structure, suggesting an unusually relaxed substrate specificity of the nonribosomal peptide synthetase that is the putative biosynthetic enzyme responsible for the corresponding amino acid incorporation.